2015
DOI: 10.1002/bit.25898
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor Entinostat enhances polymer‐mediated transgene expression in cancer cell lines

Abstract: Eukaryotic cells maintain an immense amount of genetic information by tightly wrapping their DNA around positively charged histones. While this strategy allows human cells to maintain more than 25,000 genes, histone binding can also block gene expression. Consequently, cells express histone acetyl transferases (HATs) to acetylate histone lysines and release DNA for transcription. Conversely, histone deacetylases (HDACs) are employed for restoring the positive charge on the histones, thereby silencing gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Compacted nucleosomes block gene expression by sequestering the nucleotide sequences necessary for transcription factor binding and RNA polymerase recruitment [ 22 ]. Histone acetyl transferases (HATs) and histone deacetylases (HDACs) dictate the presence of acetyl marks [ 23 , 24 ], which regulate the openness of chromatin. Thus, the processes for adding and removing these marks have become putative targets for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Compacted nucleosomes block gene expression by sequestering the nucleotide sequences necessary for transcription factor binding and RNA polymerase recruitment [ 22 ]. Histone acetyl transferases (HATs) and histone deacetylases (HDACs) dictate the presence of acetyl marks [ 23 , 24 ], which regulate the openness of chromatin. Thus, the processes for adding and removing these marks have become putative targets for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gong et al (2002) reported that DNA methylation could mediate the silencing of exogenous promoters (Gong et al, 2002). Recently, Elmer et al (2015) provided an example of histone acetylation-regulated transgene expression (Elmer et al, 2015). In this study, we found that the expression levels of FAD3 in the 35S::FAD3/gcn5 transgenic lines were lower than those in the 35S::FAD3/Ws, which resulted in differing ALA/LA ratios in the 35S::FAD3/gcn5 and 35S::FAD3/Ws plants.…”
Section: Epigenetic Regulation Of the Seed Fa Composition Might Impromentioning
confidence: 99%
“…12,13 Many DNMT inhibitors such as 5-Aza-2'-deoxycytidine and zebularine have been used to prevent methylation of DNA. 14,15 Several inhibitors of histone deacetylases (HDACs) have also been shown to increase transgene expression, including Entinostat (a HDAC 1/3 inhibitor) 16 , Tubacin (HDAC6i) 17 , Trichostatin A (HDAC6i) [18][19][20] , and Vorinostat (pan-HDACi) [21][22][23] . However, it is important to note that some of these HDAC inhibitors enhance transgene expression by influencing cytoplasmic transport instead of directly influencing histone modifications.…”
Section: Introductionmentioning
confidence: 99%